RRLC-QTOF/MS-Based Metabolomics Reveal the Mechanism of Chemical Variations and Transformations of Astragali Radix as a Result of the Roasting Process - Li, Yang; Huang, Shenhui; Sun, Jie; Duan, Weiping; Li, Cunyu; Peng, Guoping; Zheng, Yunfeng (Frontiers in Chemistry, 2022)
Astragali Radix (AR), which is extensively used as a healthy food supplement and medicinal herb, contains two forms of products corresponding to raw Astragalus Radix (RAR) and processed Astragali Radix (PAR) which is obtained by roasting. In this study, a non-targeted rapid resolution liquid chromatography coupled with quadruple time-of-flight mass spectrometry (RRLC-Q/TOF-MS) based metabolomics approach was developed to investigate the chemical changes of AR due to roasting. A total of 63 compounds were identified or tentatively identified. Among them, 23 isoflavonoids (composed of 12 isoflavones, 8 pterocarpans, and 3 isoflavans) and 6 cycloastragenols were characterized as differential metabolites. Heatmap visualization and high-performance liquid chromatography coupled with photo diode array and evaporative light scattering detector (HPLC–PDA-ELSD) quantitative analysis revealed that malonyl isoflavonoids or cycloastragenols were at higher levels in RAR. These might be converted to corresponding acetyl isoflavonoids and cycloastragenols and related isoflavonoid glycosides during roasting. To prove this prediction, chemical conversion experiments on malonyl isoflavonoids and cycloastragenols were performed to confirm and clarify the chemical transformation mechanism.